FORMULASI PEMBUATAN BISKUIT CRACKERS BERBASIS TEPUNG IKAN SIDAT - Rosmini; Nani Astria (Jurnal Ilmiah Kesmas -IJ, 2022)
Research has been carried out on the formulation for making crackers biscuit based on eel flour. Problem of low protein content and calcium crackers are supposed to be overcome by the addition or substation of wheat flour with are rich in protein and calcium. Sidat fish with rich in protein and calcium could processed to be flour and applied top processing of crackers : in assumption. This study aims to determine the effect of adding fish meal to the resulting crackers biscuit to determine and the optimal combination variation to produce crackers with good nutritional quality. This study used a Completely Randomized Design (CRD) with 5 levels, each treatment was carried out 2 replicates. The treatment in this study was in the form of adding eel flour to biscuit processing with various concentrations, namely = 0%, B = 10%, C = 20%, D = 30%, and E = 40% (by weight of wheat flour). Eel based fish meal crackers it was found that B (10% eel flour) was better than the concentration of the addition of other eel flour.